A miniaturized electron source based on dielectric laser accelerator operation at higher spatial harmonics and a nanotip photoemitter. (21st January 2016) - McNeur, Joshua; Kozak, Martin; Ehberger, Dominik; Schönenberger, Norbert; Tafel, Alexander; Li, Ang; Hommelhoff, Peter
Abstract: Here we propose a miniaturized electron source driven by recent experimental results of laser-triggered electron emission from tungsten nanotips and dielectric laser acceleration of sub relativistic electrons with velocities as low as or energies as low as 9.6 keV, less than 20% of the speed of light. The recently observed laser-triggered emission of coherent low-emittance electron pulses from tungsten nanotips naturally lends itself towards incorporation with subrelativistic dielectric laser accelerators (DLAs). These structures have previously been shown to accelerate 28 keV electrons and here we report on the utilization of the 4th and 5th spatial harmonics of near fields in the single grating DLA to achieve acceleration of electrons with kinetic energies of 15.2 and 9.6 keV. We then propose the combination of needle tip emitters with subrelativistic accelerators to form a mm-scale device capable of producing electrons with arbitrary energies.